Low Fat Premixed Mayonnaise Block Used OSA-Corn Starch as Egg Yolk Replacer Plus Corn Starch Binding Agent - Citra Pratiwi Prayitno; Agus Wijaya; Filli Pratama; Anny Yanuriati (Jurnal Teknologi dan Industri Pangan, 2022)
Mayonnaise contains a substantial amount of fat and water. Therefore, it is easily degraded during storage. Reducing fat and moisture content in mayonnaise could extend its shelf life. It can be done by replacing the egg yolk to octenyl succinic anhydride (OSA)-corn starch and then forming it as a premixed block using a binding agent. The research objective was to obtain technology for low-fat mayonnaise making by OSA-cornstarch and corn starch addition but still acceptable by consumers based on its physicochemical and sensory characteristics. The low fat premixed mayonnaise was made by mixing the egg yolks and/or OSA-corn starch, corn starch, mustard, sugar, salt, and xanthan gum. A completely randomized research design was used with three levels of OSA-corn starch (0, 25, and 50%) to replace egg yolk and its combination with corn starch as a binder agent at 43 and 50%. The parameters analyzed on the premixed mayonnaise blocks included moisture and fat content, water absorption index, and water solubility. In contrast, parameters for constituted mayonnaise were moisture content, viscosity, and hedonic sensory analysis by 25 semi-trained panelists. The constituting step of the mayonnaise was the further addition of water, oil, and lime juice before serving. The data were analyzed with ANOVA. The results showed that OSA-corn starch and corn starch addition could reduce the fat content of premixed mayonnaise by 41.7% which was obtained from 50% OSA-corn starch and addition of 43% corn starch. The resulted mayonnaise was slightly liked by the semi-trained panelists (scored 3).